Penggunaan di mana dan yang mana sebagai Kata Hubung: Analisis Linguistik Korpus (Jurnal Bahasa, 2011)
By focusing on the use of "di mana" and "yang mana" as conjunctions, this study aims to investigate the extent to which Malay writing has been influenced by English. The corpus for this descriptive study comprised online news reports of a local Malay newspaper from 1st July 2010 to 10th July 2010. The size of the corpus was around 350000 words. These were processed using the concordance program AntConc version 3.2.1w (Windows). This study shows that the use of "di mana" and "yang mana" as conjunctions in news report is ubiquitous, especially in articles; while "di mana" as a conjuction is used more frequently by reporters in the main columns. Malay speakers are generally more inclined to use "di mana" and "yang mana" as conjunctions, and the acceptance of this usage seems to be increasing. The findings also show that both "di mana" and "yang mana", when used as conjunctions are frequently followed by an independent clause, and preceded by a comma. "Di mana" is mostly used as a relative conjunction referring to activities/incidents, abstract concepts, place, time, and conditions/situations.Keywords: di mana, yang mana, connectors, linguistic corpus, AntConc concordance program